The Impact of Fissurectomy Combined with Botulinum Toxin Injection in the Treatment of Chronic Anal Fissure - Karabulut, Koray; Aygen, Erhan; Kırkıl, Cuneyt; Camcı, Cemalettin; Dogru, Osman; Esen, Kazım; Ilhan, Yavuz Selim (Fırat University, 2012)
Objective: The aim of this prospective randomized study was to determine the outcome of fissurectomy combined with botulinum toxin type-A (BTX-A) on the healing of medically resistant fissures over that achieved with BTX-A alone. Materials and Methods: A total of 36 consecutive patients with chronic anal fissure located on posterior midline who failed healing after topical medical therapy were enrolled. The patients were divided into 2 groups. The patients were divided into, BTX and BTX+fissurectomy (FIS) groups. They were clinically checked 1, 2, 4, and 8 weeks after the procedures. Symptomatic relief, early postoperative complications, clinical and anoscopic findings were recorded. The demograpic and clinical parameters were compared using Mann-Whitney U and Chi-squre tests. Results: There were no significant difference between the two groups regarding the age and gender. The most common complaints were rectal bleeding, constipation and pain during and/or after defaecation. All of the procedures performed without any postprocedural complications. Symptoms were reduced significantly with respect to the preoperative value. Symtomatic relief was assesesed in more patients in BTX+FIS group than BTX only group, but the difference was not significant. On 4th week anoscopic examination, complete healing was assesed in 14 (%77.8) and 11 (%61.1) patients in BTX+FIS and BTX groups, respectively. The median follow-up was 5 months. There was no recurrence during the follow-up. None of the patients had continence disturbance. Conclusion: Although BTX-A injection is an effective and safe treatment option in patients with a posterior chronic anal fissure non-responsive to other medical treatments, combining it with fissurectomy does not increase the healing rate.

Amaç: Bu randomize prospektif çalışmanın amacı, medikal tedaviye dirençli kronik anal fissür tedavisinde, fissürektomi ile kombine edilen botulinum toksini tip A (BTX-A) ile tek başına kullanılan BTX-A'nın etkinliklerini karşılaştırmaktır. Gereç ve Yöntem: Arka orta hatta topikal ilaç tedavisine dirençli kronik anal fissürü bulunan, 36 ardışık hasta değerlendirildi. Hastalar, BTX ve BTX+fissürektomi (FİS) olarak iki gruba ayrıldılar. Girişimlerden 1, 2, 4 ve 8 hafta sonra klinik olarak kontrol edildiler. Semptomatik düzelme, erken ameliyat sonrası komplikasyonlar, klinik ve anoskopik bulgular kaydedildi. Demografik ve klinik parametreler Mann-Whitney U ve Ki-kare testleri kullanılarak karşılaştırıldı. Bulgular: Gruplar arasında yaş ve cinsiyet açısından anlamlı fark yoktu. En sık karşılaşılan şikayetler, rektal kanama, kabızlık ve dışkılama sırasında ve/veya sonrasında ağrıydı. Girişimlerin tamamı komplikasyonsuz olarak gerçekleştirildi. İşlem öncesine kıyasla semptomlar anlamlı olarak azaldı. BTX+FİS grubunda BTX grubuna göre daha fazla hastada semptomatik düzelme sağlandı ancak aradaki fark anlamlı değildi. Dördüncü haftada yapılan anoskopik muayenede, BTX+FİS ve BTX gruplarında sırasıyla 14 (%77.8) ve 11 (%61.1) hastada fissürün tamamen iyileştiği tespit edildi. Ortanca takip süresi 5 aydı. Takip sürecinde nüks görülmedi. Hastaların hiçbirinde inkontinans ortaya çıkmadı. Sonuç: Diğer medikal tedavilere cevap vermeyen posterior kronik anal fissürde BTX-A enjeksiyonu etkili ve güvenli bir tedavi yöntemi olmakla beraber, BTX-A'ya fissürektomi eklenmesi iyileşme oranlarını arttırmamaktadır.
Kronik Anal Fissür Tedavisinde Botulinum Toksini ile Birlikte Fissürektominin Etkinliği